Proper Nutrition is the Key to the Health of Preschoolers - Botirova Latofat Luftillaevna (Genius Publishing Group, 2022)
This article is devoted to the topic of rational food consumption and its role in the body system of preschoolers. The article reveals the following questions: "What is the system of proper nutrition in kindergarten"; "What is meant by proper nutrition and what it should be for preschoolers"; "What to pay attention to when catering preschool children"; "What products are preferred when catering". The forms of work with parents are formulated, recommendations on the nutrition of children are given
Keywords: activity; energy source; mineral salts and trace elements; good appetite; individual characteristics of the child